Ammonium Salts of 5-(3-Chromenyl)-5H-chromeno[2,3-b]pyridines - Yuliya E. Ryzhkova; Artem N. Fakhrutdinov; Michail N. Elinson (Molbank, 2021)
The ammonium salts of many drugs have significantly improved the solubility and, accordingly, the bioavailability of medicinal substances in the human body. 5-(4-Hydroxy-2-oxo-2H-chromen-3-yl)-5H-chromeno[2,3-b]pyridines are potential NPY1R ligands, which are attractive for antiobesity treatment. Ammonium salts of 5H-chromeno[2,3-b]pyridines were previously unknown. In this communication, it was found that the four-component reaction of salicylaldehyde, 2-aminoprop-1-ene-1,1,3-tricarbonitrile, 4-Hydroxy-2H-chromen-2-one and amines results in the formation of ammonium salts of 5-(3-chromenyl)-5H-chromeno[2,3-b]pyridines. The structure of these previously unknown compounds was confirmed by means of 1H, 13C NMR and IR spectroscopy, mass spectrometry and elemental analysis.